Cleft Lip and Palate Repair Surgeries in a Tertiary Care Center: A Descriptive Cross-Sectional Study - Rai, Sushant; Niraula, Himalaya; Sharma, Samit; Shrestha, Jayan M; Lohani, Ishwar (Journal of Institute of Medicine Nepal, 2023)
Introduction The burden of cleft lip and palate in Nepal is high. Surgeries should be performed at the right age and weight for the safety and optimal development. We aimed to identify the socio-demographic and peri-operative attributes of cleft lip and palate patients. Methods A descriptive, cross-sectional study of cleft lip and palate surgeries conducted in Tribhuvan University Teaching Hospital, over a two-year period. Variables studied include age and weight at the time of surgery, gender, ethnicity, type of repair, other congenital defects, the length of stay, and complications. Results Overall, 28 cleft lip and palate surgeries were performed. The median age at operation of cleft lip patients was six months and of cleft palate patients was 20.5 months. The median weight in kilograms of cleft lip patients was six, whereas of cleft palate patients was 10. The male-to-female ratio among all the patients was 1.2:1. The patients hailed from all seven provinces of Nepal. For cleft lip, Millard technique 13 (93%) was most commonly performed and for cleft palate, the Bardach repair 10 (71.4%) was mostly preferred. Only two patients suffered from peri-operative complications. Conclusion Millard technique and Bardach repair were the most commonly performed surgeries for cleft lip and palate respectively. Two peri-operative complications were encountered.